Формування пам'яткоохоронної діяльності на території Харківщини в повоєнний період (1945–1953 рр.) - Ліхолєтов, Ярослав Володимирович (Дніпровський національний університет імені Олеся Гончара, 2023)
Розглянуто історію розбудови пам’яткоохоронної діяльності на території Харківщини в повоєнний період у контексті загальноукраїнської системи охорони пам’яток культурної спадщини. Проаналізовано основні архівні джерела та наукові праці, розглянуто організаційні операції становлення, напрями та форми діяльності державних органів охорони культурної спадщини, їх взаємодію з органами місцевого самоврядування сектору культури, архітектури та мистецтва. Акцентовано на правових засадах функціонування державних структур, а також стані системи охорони культурної спадщини в означений хронологічний період на загальнодержавному рівні загалом та на території Харківщини зокрема. Висвітлено ідеологічні позиції радянського режиму щодо збереження пам’яток після Другої світової війни, а також пропагандистські ідеї під час спорудження нових об’єктів, які надалі стали пам’ятками. Досліджено інформацію про перші реставраційні та відновлювальні роботи на пам’ятках культурної спадщини в цей період. Розглянуто практичну діяльність місцевих органів охорони культурної спадщини в контексті чинних нормативно-правових актів. Визначено, що протягом першого повоєнного десятиріччя Харківщина була флагманом з виявлення, обліку та збереження об’єктів культурної спадщини. Визначено, що дослідження динаміки формування пам’яткоохоронної справи в повоєнний період важливе в контексті визначення помилок і здобутків фахівців окресленого періоду, зокрема для створення єдиного дослідження з історичного пам’яткознавства, а також для подальшої послідовної реалізації новітніх заходів щодо вдосконалення українського пам’яткоохоронного законодавства.

The article examines the history of the development of monument protection activities on the territory of Kharkiv region in the post-war period, in the context of the all-Ukrainian system of protection of cultural heritage monuments. The main archival sources and scientific works were analyzed, the organizational operations of formation, directions and forms of activity of state bodies for the protection of cultural heritage, as well as their interaction with local self-government bodies in the sector of culture, architecture and art were considered. Attention is focused on the legal basis of the functioning of state structures, as well as the state of the cultural heritage protection system in the specified chronological period at the national level in general, and on the territory of Kharkiv region in particular. The ideological positions of the Soviet regime regarding the preservation of monuments after the Second World War, as well as propaganda ideas during the construction of new objects, which later became monuments, are highlighted. At that time, monumental propaganda was actively developing, as monuments that reflected historical, military and revolutionary themes were mainly discovered and taken into account. The information about the first restoration and restoration works at the monuments of cultural heritage in the post-war period was studied. The practical activity of local bodies for the protection of cultural heritage in the context of the adopted legal acts, in particular the first post-war accounting of historical and architectural monuments, is considered. It was determined that during the first post-war decade, the Kharkiv region was a leader in identifying, recording and preserving cultural heritage objects. The study of regional peculiarities of the history of mon ument protection becomes a valid condition for the creation of a thorough work on the history of Ukrainian monument protection in a regional context. The study of individual phenomena related to the dynamics of the formation of the monument protection case in the post-war period is important in the context of identifying the mistakes and achievements of specialists of the outlined period, as well as for the further consistent implementation of the latest measures to improve the Ukrainian monument protection legislation.
Formation of Monument Protection Activities in the Territory of Kharkiv Region in the Post-War Period (1945–1953)
Keywords: державні органи; охорона культурної спадщини; пам'ятка; реставрація; ідеологічна політика; пропаганда; state bodies; cultural heritage protection; monument; restoration; ideological policy; propaganda; Харківщина; повоєнний період